MULTI-FACTOR CORRELATION ANALYSIS OF URBAN LANDSCAPE NETWORK BASED ON A TOURISM CITY OF HANGZHOU, CHINA - XIUMIN, ZHAO (ASEAN Journal on Hospitality and Tourism, 2010)
Urban landscape, as an important impact factor on the quality of urban life, has been paid much attention to by citizens, governments and construction enterprises. Meanwhile, the issue that many cities follow some similar international styles degrades local customs and regional features. This trend should be pertinently analyzed and answered by researchers. Urban landscape comprises some spots and regions and is a dynamic system. Based on the current situation and academic proceedings, this research puts forward the concept of urban landscape network. By a case study of Hangzhou City construction, this paper conducts a grid analysis of the landscape grid network, and builds four sub-networks: natural scenery, historical development, road transportation, and land use. Using variance analysis, correlation analysis, multiple regression analysis, this paper examines the relationship between the four networks, and finally achieves a regression equation of the landscape network in accordance with the subjective satisfaction evaluation concerning the landscape.